(untitled) (Journal of Applied Learning and Teaching, 2023)
Many instruments have been developed to investigate the issues that influence the learners in a Collaborative Learning Approach (CLA). However, existing instruments were found inadequate to investigate important areas such as the perceptions of English as a Second Language (ESL) undergraduates in CLA, the perceptions of ESL teachers about their undergraduates in CLA, the challenges faced by ESL undergraduates in CLA, and the perceptions of ESL teachers about the challenges faced by their undergraduates in CLA in learning English. The aim of this research is, therefore, to develop and validate questionnaires for CLA to investigate these areas in learning English. The process involved reviewing the related literature, identifying several questionnaires on CLA in different contexts and then selecting suitable items from there. These items were further adapted to suit the Pakistani ESL context and the aim of this research. Five-point Likert scale questionnaire items were developed. The questionnaires were validated by a panel of three ESL experts to measure the content validity. 60 ESL undergraduates and ten ESL teachers voluntarily participated in the pilot study. Cronbach Alpha was measured to investigate the internal consistency of the questionnaires. A good to excellent Cronbach Alpha reliability was reported for the four questionnaires.